PENGARUH TEPUNG ECENG GONDOK SEBAGAI BAHAN CAMPURAN PAKAN IKAN DENGAN MENGGUNAKAN CAMPURAN PROBIOTIK BACILLUS Sp. DAN MOLASSES - Marlina, Lusi; Pamungkas, Agisna (UPPM Politeknik TEDC Bandung, 2023)
Water hyacinth with the Latin name Eichhornia crassipes is a type of aquatic plant that is generally considered a weed. Water hyacinth can be used to feed fish that are omnivorous or herbivorous. One of them is tilapia with the Latin name Oreochromis niloticus whose market demand is very much. Tilapia has a high economic value because the need for seeds and consumption continues to increase along with the number of cultivation businesses. Making feed using probiotic Bacillus Spp. and molasses prebiotics to increase the growth rate of fish. However, one of the weaknesses of water hyacinth plants is the low digestibility of the feed ingredients because they contain a lot of crude fiber. The purpose of this study is to find the effect of each experiment that will be carried out. This study uses an experimental method. This study involved six treatments, namely P1 = Feeding + Bacillus Sp. 10 mL/Kg feed + Molasses 20 mL prebiotic. P2 = Feeding + water hyacinth flour + probiotic Bacillus Sp. 10 mL/Kg of feed. P3 = Feeding + water hyacinth flour + probiotic Bacillus Sp. 10 mL mL/Kg feed and 20 mL Molasses prebiotics. P4 = Feeding + water hyacinth flour + probiotic Bacillus Sp. 20 mL/Kg of feed. P5 = Feeding + water hyacinth flour + probiotic Bacillus Sp. 20 mL/Kg feed + Molasses 40 mL prebiotic. P6 = Feeding + water hyacinth flour without the addition of Bacillus Sp. and Molasses. This research is expected to produce a good quality fish feed mixture for rearing tilapia (Oreochromis nilocticus) which achieves a protein content of at least 25% according to SNI 01-7242- 2006. The best treatment of fish growth rate was in P3 where each fish increased by 43.8%/day. Comparison of feed using 100 grams of water hyacinth flour without the addition of Bacillus Spp. and Molasses were significantly different, where the feed using water hyacinth without the addition of Bacillus Sp. and Molasses every day the growth rate of fish is 23.64%/day. While the feed that was given a mixture of water hyacinth flour, Bacillus Spp. and Molasses like P3 the growth rate is 43.8%/day